Análisis del efecto antioxidante en extractos de brotes de amaranto elicitados con metil jasmonato - Ayala Quezada, Alejandro Abraham; Valdez Arellanes, Ana Laura; Torres Contreras, Ana Mariel; Ramírez Estrada, Karla (Universidad Autónoma de Nuevo León, 2023)
Memorias